Multi-omics pan-cancer analysis reveals the diagnostic and prognostic value of C8orf76, with experimental validation of its impact on lung adenocarcinoma cell proliferation - Zhong, Xiaohong; Zhang, Zhiyong; Gao, Rongjing; Ren, Shiqi; Li, Shifang; Zhang, Miao; Fang, Jie; Hou, Yanjiao (Frontiers in Genetics, 2025)
BackgroundChromosome 8 open reading frame 76 (C8orf76) is a nuclear protein-encoding gene, has received limited attention in current study. Multi-omics pan-cancer analysis focused on the diagnosis, prognosis, immune cell infiltration, methylation, and anti-cancer drug sensitivity remains an enigma. The effect of C8orf76 on lung adenocarcinoma (LUAD) is unknown.MethodsMulti-omics pan-cancer analysis by utilizing datasets including UALCAN, TIMER 2.0, Human Protein Atlas (HPA), The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), cBioPortal, Gene Expression Profiling Interactive Analysis (GEPIA), OncoDB, and MethSurv datasets, were conducted to analyze C8orf76 across 33 cancer types. Furthermore, differential R packages were uesd for an in-depth analysis of C8orf76. The correlation between C8orf76 expression and diagnostic, prognosis, genetic alteration, mRNA modification, DNA methylation, lncRNA-miRNA-C8orf76 regulatory network, immune cell infiltration, and anti-tumor drugs response were explored to evaluate the potential roles of C8orf76. Most importantly, experiments including quantitative polymerase chain reaction (qPCR), RNA interference (RNAi), Western blotting (WB), and Edu staining, were performed for experimental verification.ResultsIt was noted that the C8orf76 expression was markedly elevated across multiple tumor types. Moreover, C8orf76 showed potential as a diagnostic and prognostic biomarker. Besides, it was confirmed that the expression of C8orf76 was related to DNA methylation, mRNA modification, and the infiltration of immune cells. The lncRNA-miRNA-C8orf76 network was established in the study of LUAD. Experimental validation in LUAD A549 cells demonstrated that the knockdown of C8orf76 significantly inhibited cell proliferation in LUAD.ConclusionThe present study is the first to report that the multi-omics pan-cancer analysis predicts C8orf76 as a promising target in cancer prognosis, diagnosis, immunology, and chemotherapy, highlighting its influence on cell proliferation in LUAD with experimental validation.